2019
DOI: 10.1371/journal.pone.0218654
|View full text |Cite
|
Sign up to set email alerts
|

Delivering community-led integrated HIV and sexual and reproductive health services for sex workers: A mixed methods evaluation of the DIFFER study in Mysore, South India

Abstract: Introduction Women in developing countries continue to face barriers to accessing sexual and reproductive health (SRH) services, with marginalized women facing increased challenges to accessing care. The Diagonal Interventions to Fast-Forward Enhanced Reproductive Health (DIFFER) project implemented a package of interventions for female sex workers and women from the general population which integrated horizontal health services for the general population with existing vertical targeted interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Reza‐Paul et al, in their study analysing the impact of integrating services for FSWs with HIV in India, measured the rate of contraception use after integration. Although there was already a high rate of contraception use at baseline (98%), by the end of the study they noted an increase in hormonal contraception methods (0.6–11%, p = 0.003) [10].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Reza‐Paul et al, in their study analysing the impact of integrating services for FSWs with HIV in India, measured the rate of contraception use after integration. Although there was already a high rate of contraception use at baseline (98%), by the end of the study they noted an increase in hormonal contraception methods (0.6–11%, p = 0.003) [10].…”
Section: Resultsmentioning
confidence: 99%
“…Reza‐Pual et al’s ‘well woman clinic’ in India found a significant increase in cervical cytology and treatment after integrating services into their HIV clinic for FSWs (11.5–56%, p < 0.001) [10]. Two audits from the UK showed increased rates of cervical smears among women with HIV after integration of services [11,12].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PEPFAR recognized the need to increase focus on KPs when it launched the Key Populations Investment Fund (KPIF) in 2016 [9]. The KPIF is a US$100 million additional investment into KP‐specific programmes meant to close some of the persistent gaps in access to services and follow the evidence that KP‐led organizations are critical partners [10‐12].…”
Section: Introductionmentioning
confidence: 99%
“…However, condom use continues to remain low with regular partners, such as husbands and boyfriends (Deering et al, 2011;Fehrenbacher et al, 2018;Isac et al, 2017). The results from various surveys in Mysore show that while reported condom use is high in the last sex act with occasional clients, consistent condom use with all clients and partners continues to be a challenge (Reza-Paul et al, 2008;Reza-Paul et al, 2019). PrEP now presents a potential means of addressing this gap (Mayer, Chandhiok, & Thomas, 2016).…”
Section: Introductionmentioning
confidence: 99%